An optimal exercise protocol for improving endurance performance and health - Hiroaki Tanaka; Kazuhiro Morimura; Keisuke Shiose (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Recent evidence suggests that the underlying mechanisms involved in beneficial adaptations to aerobic exercise, which promote health and increase endurance capacity, may be due to exercise-induced transient gene responses. In this review, an efficient exercise protocol to promote health and increase endurance capacity is discussed in relation to exercise-induced changes in gene expression. Exercise-induced transient gene responses, which are associated with adaptations to aerobic exercise, have been suggested to be induced by metabolic stress. Exercise to increase aerobic capacity and improve health should aim to increase the expression of peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α), which is the key gene to enhance the function of mitochondria. Training at the lactate threshold is suggested to be the threshold intensity for inducing gene expression of PGC-1α. Analysis of training studies assessing the effect on VO2max suggests that individuals with varied baseline VO2max values obtain significant improvement in VO2max at the lactate threshold. High-intensity interval training (HIT), which can induce gene expression of PGC-1α, may be as efficient and effective in increasing aerobic capacity as continuous exercise training, despite a substantial reduction in exercise volume. Exercise at times when muscle glycogen is low could be more effective at improving mitochondrial function. HIT consumes a large amount of muscle glycogen per unit of energy consumption, and studies suggest that longer recovery periods induce glycogen depletion with much lower amounts of exercise compared to continuous exercise. Exercise after HIT-induced glycogen depletion may be a beneficial exercise prescription for endurance capacity and health promotion.